Droplet manipulation with bioinspired liquid-infused surfaces: A review of recent progress and potential for integrated detection. (February 2019) - Regan, Daniel P.; Howell, Caitlin
Abstract: Point-of-need (PON) diagnostics offer promising methods to gather information relevant to health and safety on-site without the requirement for a fully equipped laboratory. In this review, we discuss how liquid-infused surfaces offer a promising platform to expand the capabilities of PON devices in the areas of biological sample preparation and system integration, providing new methods of controlling the movement of droplets and facilitating detection of biological and chemical compounds contained therein. Modifications to the underlying surface structure can be used to passively control the direction of droplet movement, and the careful selection of responsive solid substrates and/or overlying liquids can allow active control through induced temperature gradients, electrical stimulation, and exposure to magnetic fields. Recent work leveraging other advantages of liquid-infused systems such as ultra-low friction, noncoalescence of droplets, and liquid–liquid patterning has demonstrated the unique ways in which this approach can be used to both enhance current detection methods as well as enable new ones. Together, these recent developments in the manipulation of droplets on liquid-infused surfaces point to their significant potential for furthering the capacity of PON devices for both biological and environmental samples. Graphical abstract: Image 1